The MONDO Tracker: Characterisation and Study of Secondary Ultrafast Neutrons Production in Carbon Ion Radiotherapy - Toppi, Marco; Battistoni, Giuseppe; Bochetti, Alessandro; De Maria, Patrizia; De Simoni, Micol; Dong, Yunsheng; Fischetti, Marta; Franciosini, Gaia; Gasparini, Leonardo; Magi, Marco; Manuzzato, Enrico; Mattei, Ilaria; et al. (Frontiers in Physics, 2020)
Secondary neutrons produced in Particle Therapy (PT) treatments are responsible for the delivery of a large fraction of the out-of-target dose as they feebly interact with the patient body. To properly account for their contribution to the total dose delivered to the patient, a high precision experimental characterisation of their production energy and angular distributions is eagerly needed. The experimental challenge posed by the detection and tracking of such neutrons will be addressed by the MONDO tracker: a compact scintillating fibres detector exploiting single and double elastic scattering interactions allowing for a complete neutron four momentum reconstruction. To achieve a high detection efficiency while matching the fibres (squared, 250 μm side) high granularity, a single photon sensitive readout has been developed using the CMOS based SPAD technology. The readout sensor, with pixels of 125×250 ^2 size, will be organised in tiles covering the full detector surface and will implement an auto-trigger strategy to identify the events of interest. The expected detector performance in the context of neutron component characterisation in PT treatments delivered using carbon ions has been evaluated using a Monte Carlo simulation accounting for the detector response and the neutrons production spectra.